In-depth drug delivery to tumoral soft tissues via pH responsive hydrogel - Sarwar, Shumaila; Bashir, Sajid; Asim, Mulazim Hussain; Ikram, Fakhera; Ahmed, Arsalan; Omema, Ume; Asif, Anila; Chaudhry, Aqif Anwar; Hu, Yong; Ustundag, Cem Bulent (ROYAL SOC CHEMISTRY, 2022)
A pH responsive nanoparticle-hydrogel hybrid drug delivery system was investigated for in-depth anticancer drug delivery to solid tumours. It consists of acid susceptible polymer nanoparticles loaded in a chitosan hydrogel. The hybrid formulation was characterized by UV-visible spectroscopy, FTIR, SEM, TEM, particle size analysis, zeta potential measurement and viscosity measurement. Drug encapsulation and nanoparticle loading efficiencies were found to be 48% and 72% respectively which describes the efficient interaction of the chemical entities in this hybrid drug delivery system. The hydrogel exhibited pH responsive behaviour: minimal drug and nanoparticle release at physiological pH but an increase in viscosity under acidic conditions and fast nanoparticle and drug release. The cytotoxicity of the drug loaded hydrogel was investigated against the MCF-7 breast cancer cell line along with the drug and nanoparticles without hydrogel. The drug loaded hydrogel showed a better cytotoxic effect on MCF-7 cancer cells. Thus, drug loaded nanoparticles containing hydrogel could be a better option for maximum drug distribution in tumours.
Keywords: NANOPARTICLES; CHITOSAN; RELEASE; MICELLE; PHARMACOKINETICS; PENETRATION; DOXORUBICIN; EFFICIENCY; SYSTEMS; Chemistry